2017
DOI: 10.1007/s00299-017-2117-0
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the overexpression of a tomato translationally controlled tumor protein (TCTP) in tobacco revealed by phenotypic and transcriptomic analysis

Abstract: Overexpression of a tomato TCTP impacts plant biomass production and performance under stress. These phenotypic alterations were associated with the up-regulation of genes mainly related to photosynthesis, fatty acid metabolism and water transport. The translationally controlled tumor protein (TCTP) is a multifaceted and highly conserved eukaryotic protein. In plants, despite the existence of functional data implicating this protein in cell proliferation and growth, the detailed physiological roles of many pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…The importance of TCTP in biological stress reactions was also demonstrated in non-mammalian systems. De Carvalho et al overexpressed TCTP from tomatoes in tobacco plants, which resulted in an increased growth rate and an improved performance under salt and osmotic stress conditions [48]. The transgenic plants displayed an increased expression of genes involved in photosynthesis, fatty acid metabolism, and water transport, and this was paralleled by an increased photosynthetic rate.…”
Section: Biological Stress Reactions and Autophagymentioning
confidence: 99%
“…The importance of TCTP in biological stress reactions was also demonstrated in non-mammalian systems. De Carvalho et al overexpressed TCTP from tomatoes in tobacco plants, which resulted in an increased growth rate and an improved performance under salt and osmotic stress conditions [48]. The transgenic plants displayed an increased expression of genes involved in photosynthesis, fatty acid metabolism, and water transport, and this was paralleled by an increased photosynthetic rate.…”
Section: Biological Stress Reactions and Autophagymentioning
confidence: 99%
“…A new study extended these investigations. De Carvalho and colleagues expressed tomato TCTP in tobacco plants and, by transcriptomics analysis, studied the pathways that are differentially regulated as a result of TCTP overexpression (de Carvalho et al 2017). They observed that genes involved in photosynthesis, fatty acid metabolism and water transport are up-regulated, while genes involved in the synthesis of the phytohormone ethylene were downregulated.…”
Section: Note Added In Proofmentioning
confidence: 99%
“…The importance of TCTP in abiotic stress response of plants has been reported not only for its differential expression (Ermolayev et al, 2003;Vincent et al, 2007;Guo et al, 2012), but also by recombinant protein functional analysis in a host organism (Wang et al, 2012;Santa Brígida et al, 2014) and evaluation by silencing (Cao et al, 2012) and/or over-expression (Kim et al, 2012;Wang et al, 2015;de Carvalho et al, 2017) in transgenic plants. As example, cabbage plants silenced for the BoTCTP gene presented vegetative growth reduction and decrease of cold, high temperature and salinity tolerance (Cao et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies have reported the TCTP roles in response to abiotic stresses by its increased transcript levels under salt stress (Qin et al, 2011;Guo et al, 2012;Li et al, 2013;Santa Brígida et al, 2014), extremes of temperature (Cao et al, 2010), drought (Kim et al, 2012), and mercury (Wang et al, 2015) stress conditions. In addition, the TCTP relationship with abiotic stress has been also evidenced by silencing (Cao et al, 2010) and/or over-expression (Kim et al, 2012;Wang et al, 2015;de Carvalho et al, 2017) of TCTP genes in transgenic plants.…”
Section: Introductionmentioning
confidence: 99%